2022
DOI: 10.1021/acs.jnatprod.2c00706
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Stress-Induced Metabolites in Escherichia coli

Abstract: Escherichia coli isolates commonly inhabit the human microbiota, yet the majority of E. coli’s small-molecule repertoire remains uncharacterized. We previously employed erythromycin-induced translational stress to facilitate the characterization of autoinducer-3 (AI-3) and structurally related pyrazinones derived from “abortive” tRNA synthetase reactions in pathogenic, commensal, and probiotic E. coli isolates. In this study, we explored the “missing” tryptophan-derived pyrazinone reaction and characterized tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Besides, the stretching vibration peak of aldehyde (−CHO) for monomers at 1665 cm −1 disappeared, thereby suggesting that the highly polymerization degree was achieved for these COFs. 84,85 In addition, the peaks between 124.0 and 133.4 ppm in 13 C CP/MAS NMR of two carbon atoms of C�C further confirmed the formation of vinylene linkage (Figure S2). 86−88 Meanwhile, the peaks around 176.3, 176.6, and 177.8 ppm were attributed to the carbon atoms of the triazine ring, and the peaks around 152.3, 129.1, and 117.7 ppm were attributed to the adjacent carbon atoms with F, Cl, and Br atoms, respectively, thereby indicating that the triazine ring and the halogen atoms were successfully introduced into the skeleton.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Besides, the stretching vibration peak of aldehyde (−CHO) for monomers at 1665 cm −1 disappeared, thereby suggesting that the highly polymerization degree was achieved for these COFs. 84,85 In addition, the peaks between 124.0 and 133.4 ppm in 13 C CP/MAS NMR of two carbon atoms of C�C further confirmed the formation of vinylene linkage (Figure S2). 86−88 Meanwhile, the peaks around 176.3, 176.6, and 177.8 ppm were attributed to the carbon atoms of the triazine ring, and the peaks around 152.3, 129.1, and 117.7 ppm were attributed to the adjacent carbon atoms with F, Cl, and Br atoms, respectively, thereby indicating that the triazine ring and the halogen atoms were successfully introduced into the skeleton.…”
mentioning
confidence: 69%
“…Experimental procedures, materials and synthetic procedures, supporting figures, typical procedure for the products, and copies of 1 H and 13 C NMR spectra for the products (PDF)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1‐5 ] Although the detailed pathogenesis of psoriasis is still unclear, it is generally accepted that the pathogenesis of psoriasis is stimulated by keratinocyte hyperproliferation and excessive inflammatory response. [ 6‐10 ] Previous studies have shown that multiple cytokines, such as interleukin (IL)‐17 and tumor necrosis factor‐alpha (TNF‐ α ) are involved in the pathogenesis of psoriasis vulgaris. [ 11‐15 ] TNF‐ α, mainly derived from activated macrophages and monocytes, is an inflammatory cytokine produced during acute inflammation that can promote the proliferation and release of cytokines in epidermal keratinocytes.…”
Section: Background and Originality Contentmentioning
confidence: 99%